2016
DOI: 10.1080/10942912.2015.1031246
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Physico-Chemical, Thermal, and Oxidative Properties of Winged Bean and Soybean Oils

Abstract: To explore possible food applications, the oxidative stability, antioxidants contents (tocopherols and tocotrienols), thermal properties, and solid fat content of winged bean oil were investigated along with soybean oil for comparison. Results showed that winged bean oil was significantly (p < 0.05) resistant to oxidation (27 h) compared to soybean oil (9 h) heated at 110 o C for 32 h, due presumably to the presence of alpha tocotrienol and the high behemic acid content. The high content of tocopherols, 230 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…However, winged bean oil has more saturated fatty acids, thereby making it less preferred. A recent study of the physicochemical properties of winged bean oil found that fatty oil extraction using hexane, which is the most common industrial extraction process, agrees with all edible characteristics and fatty acid compositions [21]. In another study, winged bean oil was superior to soybean oil as a result of its high oxidative strength, solid fat content, and good thermal conductivity, thereby making it suitable for frying food [21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, winged bean oil has more saturated fatty acids, thereby making it less preferred. A recent study of the physicochemical properties of winged bean oil found that fatty oil extraction using hexane, which is the most common industrial extraction process, agrees with all edible characteristics and fatty acid compositions [21]. In another study, winged bean oil was superior to soybean oil as a result of its high oxidative strength, solid fat content, and good thermal conductivity, thereby making it suitable for frying food [21].…”
Section: Discussionmentioning
confidence: 98%
“…e result obtained for the tubers (Table 5) ranged from 0.21 (Tpt16) to 4.53 (Tpt33). Due to its high thermal conductivity and oxidative features, winged bean oil is valuable as a frying medium when compared to soybean oil [21]. However, winged bean oil has more saturated fatty acids, thereby making it less preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterols, such as b-sitosterol, campesterol, and stigmasterol, are natural ingredients found in plant cell membranes and have high contents in vegetable Roche et al, (2016), and others from He et al, (2017), Makeri et al, (2015), Ozkan et al, (2017), Gong et al, (2013), andZhang et al, (2011). All data came from different samples, measured three times in parallel and results are shown as means ± standard deviation.…”
Section: Phytosterol Compositionmentioning
confidence: 99%
“…In addition, molecular composition with long-chain fatty acids imparts higher melting and crystallization temperatures than shorter chain fatty acids. [32] Figure 4b shows crystallization curves of AMF, Lipozyme-435-, and Novozyme-435-treated AMF. The crystallization curve for AMF depicts a broad range between −34.96°C and 13.86°C and short arm between 13.86°C and 15.53°C.…”
Section: Triacylglycerolsmentioning
confidence: 99%
“…Previously, it has been reported that the formation of small crystal nucleus and large surface area as a result of changing β to βʹ form enables the inclusion of air into shortenings thus improving the creaming properties of mixtures. [30,32,34,36]…”
Section: Triacylglycerolsmentioning
confidence: 99%